2001
DOI: 10.1210/endo.142.11.8478
|View full text |Cite
|
Sign up to set email alerts
|

Liver-Derived IGF-I Regulates GH Secretion at the Pituitary Level in Mice

Abstract: We have reported that liver-specific deletion of IGF-I in mice (LI-IGF-I-/-) results in decreased circulating IGF-I and increased GH levels. In the present study, we determined how elimination of hepatic IGF-I modifies the hypothalamic-pituitary GH axis to enhance GH secretion. The pituitary mRNA levels of GH releasing factor (GHRF) receptor and GH secretagogue (GHS) receptor were increased in LI-IGF-I-/- mice, and in line with this, their GH response to ip injections of GHRF and GHS was increased. Expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(34 citation statements)
references
References 50 publications
1
33
0
Order By: Relevance
“…These results, taken together with the current observations, suggest that even under normal conditions, regulation of GH, GHRH-R and GHS-R expression is under direct tonic inhibition by low circulating levels of free IGF-I. This notion is consistent with the observation that circulating GH and pituitary GHRH-R and GHS-R mRNA levels are elevated in liverspecific IGF-I knockout mice, where circulating IGF-I levels are less than 10% of normal controls, while hypothalamic GHRH or SST expression do not differ from controls (Sjogren et al 1999, Yakar et al 1999, Wallenius et al 2002. It has also been hypothesized that suppression of free IGF-I levels observed following fasting and increases in free IGF-I reported in obesity may play a role in the reciprocal changes in GH output in these extreme metabolic conditions (for review, see Frystyk 2004).…”
Section: Direct Effects Of Igf-i and Insulinsupporting
confidence: 86%
“…These results, taken together with the current observations, suggest that even under normal conditions, regulation of GH, GHRH-R and GHS-R expression is under direct tonic inhibition by low circulating levels of free IGF-I. This notion is consistent with the observation that circulating GH and pituitary GHRH-R and GHS-R mRNA levels are elevated in liverspecific IGF-I knockout mice, where circulating IGF-I levels are less than 10% of normal controls, while hypothalamic GHRH or SST expression do not differ from controls (Sjogren et al 1999, Yakar et al 1999, Wallenius et al 2002. It has also been hypothesized that suppression of free IGF-I levels observed following fasting and increases in free IGF-I reported in obesity may play a role in the reciprocal changes in GH output in these extreme metabolic conditions (for review, see Frystyk 2004).…”
Section: Direct Effects Of Igf-i and Insulinsupporting
confidence: 86%
“…However, in the adult rGhp-Cre transgenic mice, only 10% of lactotrophs are derived from somatotrophs (Luque et al 2007). In this study, GH cells in IGF1KO mice were already increased at day 10 because of the absence of the IGF1 negative feedback loop that suppressed GH production (Wallenius et al 2001). An increase of GH cells may be due to the mass differentiation of progenitor cells to GH cells, therefore, it may result in suppression of PRL cell differentiation in IGF1KO mice because PRL cells and GH cells are derived from the same origin.…”
Section: Discussionmentioning
confidence: 51%
“…Circulating IGF1 produced in the liver acts as a mediator of GH action and regulates systemic growth (D'Ercole et al 1984). In the regulation of GH synthesis and release, IGF1 specifically inhibits GH gene transcription and secretion by negative feedback mechanisms (Wallenius et al 2001). Therefore, high blood GH levels are induced by severe IGF1 deficiency (Lembo et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The fasting-induced increase in GHRH sensitivity is associated with an increase in pituitary GHRH receptor (GHRH-R) mRNA and an increase in pituitary GHRH binding (Sugihara et al 1996), with a concomitant decline in pituitary SRIF receptor expression and ligand binding (Bruno et al 1994). The rise in GHRH-R mRNA may be mediated by the reduction in GH/IGF-I negative feedback since IGF-I has been shown to suppress directly GHRH-R mRNA levels in primary pituitary cell cultures (Sugihara et al 1999), and we have observed an increase in GHRH-R mRNA in rats with isolated GH deficiency (spontaneous dwarf rats (SDR)) (Kamegai et al 1998a) and in mice with reduced circulating IGF-I (liver-specific IGF-I knockout mice) (Wallenius et al 2002). In order to test whether fastinginduced fall in GH/IGF-I is responsible for fastinginduced changes in pituitary receptor expression, we compared the hypothalamic/pituitary response to fasting in normal rats and GH-deficient SDR.…”
Section: Introductionmentioning
confidence: 90%